Feeding ecology and mating system in the Arctic Fox (Vulpes lagopus) - Martinez, Javier Sierro, 1991- (2012)
The arctic fox is a polar species adapted to one of the harshest environments on earth. It is a canid which lives in extremely different conditions compared to other members of its family. Usually it is used to be assumed that the variety of behaviors found in nature come from different sets of environmental conditions. Each species adapts to a particular ecological niche with a large amount of specific behaviors, strategies and tactics. In this paper a few studies in the arctic fox are summarize and put together. Thus, this species behavior is tackle from an intraspecific comparative approach to determine which ecological conditions lead the arctic fox to behave as it does. In particular, the arctic fox is a special case since there are some isolated populations with different environmental and life constraints. Comparing and contrasting this different conditions and taking into account different strategies performed in each population would come to a better understanding of this species. Thereupon, differences in its mating system, its reproductive strategy and its feeding ecology will be compared.